TIME MANAGEMENT FOR ESL TEACHERS: PROBLEMS AND SOLUTIONS (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
Time management is a major challenge for ESL (English as a Second Language) teachers, who are often busy with lesson planning, assessment, administrative tasks, student communication, and personal responsibilities. This article analyzes the main time management challenges faced by ESL teachers and provides useful solutions for effectively organizing their time. It emphasizes the need to use strategies such as effective lesson planning, prioritizing tasks, reducing administrative burdens, and optimizing time in the classroom and in travel. Through these solutions, ESL teachers will be able to improve their performance, reduce stress, and maintain work-life balance. The article also emphasizes supporting schools by reducing administrative tasks and providing support to teachers.